Role of flushing on some semen characteristics and copulating behavior in local black bucks - Mohammed, Zhina Abbas; Maarof, Nazhad N.; Omar, Chowman Aladin. (Sulaimani Journal for Pure and Applied Sciences, 2018)
This study was conducted at the animal farm, department of animal science (Bakrajo field), College of Agricultural Sciences, University of Sulaimani, Kurdistan region–Iraq, to find out the reproductive performance and evaluation of semen in a local black buck and their relation to different levels of nutrition . Eighteen local black goats (6 bucks+12 does), 1.5-2 years old were used and randomly divided into two groups (3 bucks+6 does).The groups were fed two levels, 300gm/day (0.9 Mcal ME) as low-level feed and 600gm/day (1.8Mcal ME) as high-level feed for 2 months of the mating season. The live body weight (LBW), buck semen characteristics and reproduction performance was measured through this experiment. Behavior data were collected during hand–mating, which include Copulation number and the period between two copulations (C-C), the period between first meeting and copulation (M-C), the courtship behavior index value of bucks (CBIVB) and mounting behavior of buck. The results obtained revealed no differences in LBW of bucks fed with either low or high level of concentrates during flushing period. The characteristics of buck semen in local black goat were not significantly different at all period of flushing, except live sperm percentage was significantly (P≤0.05) in a high level of treatment at a period to flushing and significant improvement (P≤0.05) in color in a period after flushing. The results of buck behavior revealed no significant differences between breeding groups. But flushing decreases the reacting time and ejaculation time when matting between does fed high level (H) and bucks fed low (L) and high level (H). The period between two copulation (C-C) recorded shorter time when mating does flushing high-level feed (H) with bucks fed low (HxL: 286.66 sec.) and high level (HxH: 405.00 sec.).
Keywords: Local Black Buck; Copulations; Semen Characteristic; Breeding Groups; Reacting Time